Screen printing ink composition and method for producing printed matter

JP7610454B2Active Publication Date: 2025-01-08NICHIAS CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021057752
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-01-08
Estimated Expiration
2041-03-30

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、スクリーン印刷用インク組成物を構成する溶媒として、(c)ゴム形成成分を溶解させる主溶媒とともに、(d)主溶媒に溶解しゴム形成成分には溶解しない貧溶媒を採用することにより、インク組成物中におけるゴム形成成分の凝集性を向上させ、スクリーン版への付着性を低減しその押出性を向上させて、印刷不良を低減することができる。 また、本発明によれば、25℃の温度下においてE型粘度計によって得られるスクリーン印刷用インク組成物の粘度(0.1/s)が300~50000Pa·sであることにより、印刷ダレを好適に抑制することができ、25℃の温度下においてE型粘度計によって得られるスクリーン印刷用インク組成物の粘度(10/s)が50~1500Pa·sであることにより、印刷姓を好適に担保することができる。 さらに、本発明によれば、25℃の温度下においてE型粘度計によって得られるスクリーン印刷用インク組成物の損失正接(0.1rad/s)が10.0~20.0であることにより、インク組成物のスクリーン版への付着性が低減されその押し出し性が向上することにより、印刷不良の発生を一層効果的に抑制することができる。 このため、本発明によれば、厚みの厚い印刷物を形成した場合においても、印刷物に印刷不良や表面荒れを生じ難いスクリーン印刷用インク組成物および係るスクリーン印刷用インク組成物を用いた印刷物の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610454000002
    Figure 0007610454000002
  • Figure 0007610454000003
    Figure 0007610454000003
  • Figure 0007610454000001
    Figure 0007610454000001
Patent Text Reader

Abstract

To provide an ink composition for screen printing which hardly causes printing defects or surface roughness on a printed matter even when a thick printed matter is formed.SOLUTION: There is provided an ink composition for screen printing which comprises (a) a rubber-forming component, (b) a crosslinking agent, (c) a main solvent for dissolving a rubber-forming component and (d) a poor solvent which dissolves in a main solvent and does not dissolves the rubber-forming component, wherein the viscosity (0.1 / s) obtained by an E-type viscometer at a temperature of 25°C is 300 to 50000 Pa s, the viscosity (10 / s) obtained by the E-type viscometer at a temperature of 25°C is 50 to 1500 Pa s and the loss tangent (0.1 rad / s) obtained by the E-type viscometer at a temperature of 25°C is 10 to 20.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ink composition for screen printing and a method for producing a printed matter. [Background technology]

[0002] In a fuel cell consisting of a stacked structure of multiple cells, it is known that a gasket with a flat upper surface made of a rubber material or a synthetic resin material having rubber-like elasticity is provided on the surface of a substrate such as a separator that constitutes the fuel cell in order to seal out hydrogen gas, oxygen gas, etc.

[0003] Although the above-mentioned gasket can be manufactured by a press molding method, an injection molding method, etc., a manufacturing method using screen printing has been proposed taking into consideration the takt time, etc. (see, for example, Patent Document 1 (JP 2008-34383 A)). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-34383 A Summary of the Invention [Problem to be solved by the invention]

[0005] When the gasket is formed by screen printing, the following steps (1) to (3) are carried out. (1) As shown in the schematic cross-sectional view of Figure 1, a screen plate S having a mask M with a predetermined pattern of openings O for applying paste corresponding to the planar shape of the gasket is placed on the lower side of a screen S1 made of stainless steel mesh or the like, and a substrate B is positioned and abutted against the lower part of the screen plate S. (2) A paste 1 made of an uncrosslinked rubber material for gasket molding is supplied to the top of the screen plate S, and is pushed out into the paste application opening O of the mask M by the movement of the squeegee R, so as to adhere to the surface of the substrate B. The substrate B is then separated from the screen plate S, and a paste application layer P is formed on the surface of the substrate B in a predetermined printing pattern, as shown in the schematic cross-sectional view corresponding to Figure 2. (3) The coating layer P is cured by heat or the like, thereby forming a gasket (having a shape corresponding to the coating layer P) integrally on the substrate 1.

[0006] Meanwhile, there is a demand for the gaskets to be relatively thick, about 90 μm to 100 μm or more.

[0007] However, the inventors have found through their investigations that when attempting to manufacture a thick gasket by screen printing using an ink composition with a relatively low viscosity (a paste made of an uncrosslinked rubber material), the ink composition tends to adhere to the screen and becomes difficult to extrude, making printing defects such as printing sagging more likely to occur.

[0008] Therefore, it was considered to use an ink composition with high thixotropy or a high viscosity as an ink composition for screen printing (a paste made of an uncrosslinked rubber material). However, after investigations by the present inventors, it was found that when an ink composition with high thixotropy or a high viscosity ink composition is used, surface roughness such as mesh marks (screen marks) is likely to occur on the surface of the obtained gasket, making it likely to result in poor appearance and poor performance.

[0009] Under these circumstances, an object of the present invention is to provide an ink composition for screen printing that is unlikely to cause printing defects or surface roughness in printed matter even when a thick printed matter is formed, and a method for producing a printed matter using the ink composition for screen printing. [Means for solving the problem]

[0010] In order to achieve the above-mentioned object, the present inventors have conducted intensive research and have found that the above technical problems can be solved by a screen printing ink composition which contains (a) a rubber-forming component, (b) a crosslinking agent, (c) a main solvent that dissolves the rubber-forming component, and (d) a poor solvent that dissolves in the main solvent but not in the rubber-forming component, and which has a viscosity (0.1 / s) of 300 to 50,000 Pa s measured at 25°C using an E-type viscometer, a viscosity (10 / s) of 50 to 1,500 Pa s measured at 25°C using an E-type viscometer, and a loss tangent (0.1 rad / s) of 10 to 20 measured at 25°C using an E-type viscometer, and have completed the present invention based on this finding.

[0011] That is, the present invention provides (1)(a) a rubber-forming component; (b) a cross-linking agent; (c) a primary solvent for dissolving the rubber-forming components; (d) a poor solvent that is soluble in the main solvent but not in the rubber-forming component; Including, The viscosity (0.1 / s) measured by an E-type viscometer at a temperature of 25°C is 300 to 50,000 Pa s. The viscosity (10 / s) measured using an E-type viscometer at a temperature of 25°C is 50 to 1500 Pa s. The loss tangent (0.1 rad / s) obtained by an E-type viscometer at a temperature of 25°C is 10.0 to 20.0. A screen printing ink composition comprising: (2) A method for producing a printed matter, comprising screen-printing the screen printing ink composition according to (1) above, followed by a curing treatment to form a printed matter. (3) The method for producing a printed matter according to (2) above, wherein the printed matter is a gasket. This provides: In the following, (c) a main solvent that dissolves the rubber-forming components will be referred to as "(c) main solvent" and (d) a poor solvent that dissolves in the main solvent but not the rubber-forming components will be referred to as "(d) poor solvent" as appropriate. Effect of the Invention

[0012] According to the present invention, by employing, as the solvents constituting the screen printing ink composition, (c) a main solvent that dissolves the rubber-forming component, and (d) a poor solvent that dissolves in the main solvent but not in the rubber-forming component, it is possible to improve the cohesiveness of the rubber-forming component in the ink composition, reduce adhesion to the screen stencil, improve extrudability, and reduce printing defects. Furthermore, according to the present invention, the viscosity (0.1 / s) of the screen printing ink composition measured at 25°C using an E-type viscometer is 300 to 50,000 Pa s, thereby making it possible to suitably suppress printing sagging, and the viscosity (10 / s) of the screen printing ink composition measured at 25°C using an E-type viscometer is 50 to 1,500 Pa s, thereby making it possible to suitably ensure printability. Furthermore, according to the present invention, the loss tangent (0.1 rad / s) of the screen printing ink composition measured with an E-type viscometer at a temperature of 25°C is 10.0 to 20.0, thereby reducing the adhesion of the ink composition to the screen stencil and improving the extrusion properties, thereby making it possible to more effectively suppress the occurrence of printing defects. Therefore, according to the present invention, it is possible to provide an ink composition for screen printing that is unlikely to cause printing defects or surface roughness in printed matter even when a thick printed matter is formed, and a method for producing a printed matter using the ink composition for screen printing. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic cross-sectional view for explaining a printing method by screen printing. FIG. [Diagram 2] FIG. 2 is a schematic cross-sectional view for explaining a printed matter obtained by screen printing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The screen printing ink composition according to the present invention comprises: (a) a rubber-forming component; (b) a cross-linking agent; (c) a primary solvent for dissolving the rubber-forming components; (d) a poor solvent that is soluble in the main solvent but not in the rubber-forming component; Including, The viscosity (0.1 / s) measured by an E-type viscometer at a temperature of 25°C is 300 to 50,000 Pa s. The viscosity (10 / s) measured using an E-type viscometer at a temperature of 25°C is 50 to 1500 Pa s. The loss tangent (0.1 rad / s) obtained by an E-type viscometer at a temperature of 25°C is 10 to 20. It is characterized by the above.

[0015] In the screen printing ink composition according to the present invention, (a) the rubber-forming component means (a-1) a rubber component alone, or (a-2) a mixture of a rubber component and a plasticizer.

[0016] In the screen printing ink composition according to the present invention, the rubber component constituting the rubber-forming component (a) can specifically be one or more selected from silicone rubber, acrylic rubber, chloroprene rubber, polysulfide rubber, urethane rubber, butyl rubber, natural rubber, ethylene-propylene rubber, nitrile rubber, fluororubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene rubber, chlorosulfonated polyethylene rubber, polyisobutylene, modified silicone and the like, preferably one or more selected from ethylene-propylene-diene rubber, fluororubber and acrylonitrile-butadiene rubber, more preferably ethylene-propylene-diene rubber.

[0017] In the screen printing ink composition according to the present invention, when the rubber-forming component (a) comprises a mixture of the rubber component (a-2) and a plasticizer, the plasticizer is not particularly limited as long as it is capable of adjusting the polymer viscosity of the rubber-forming component within a desired range, and can be appropriately selected from among known plasticizers or softeners for rubber. Specific examples of the plasticizer constituting the rubber-forming component, when the rubber component is ethylene-propylene-diene rubber (EPDM), include one or more selected from ethylene-propylene rubber (EPM), fatty acid esters, phthalic acid esters, aliphatic dibasic acid esters, phosphate esters, trimellitic acid esters, polyesters, linosyl acid esters, acetate esters, mineral oils, etc.

[0018] In the screen printing ink composition according to the present invention, the polymer viscosity (0.1 rad / s) of the rubber-forming component (a) is preferably 2000 to 50000 Pa·s, more preferably 10000 to 45000 Pa·s, and even more preferably 10000 to 40000 Pa·s.

[0019] In the screen printing ink composition according to the present invention, since the polymer viscosity (0.1 rad / s) of the rubber-forming component (a) is within the above range, when the ink composition is extruded from a screen printing stencil and the extrudate is then dried or the crosslinking agent is heat-cured, the viscosity of the extrudate can be easily reduced to a desired range and the leveling properties (surface smoothness) of the extrudate can be easily improved.

[0020] In this application, the polymer viscosity (0.1 rad / s) of the rubber-forming component refers to the value obtained by dissolving the polymer-forming component in a main solvent, drying it with hot air at 60°C for 12 hours or more to completely remove the solvent, and then measuring the viscosity using an E-type viscometer (Anton Paar rheometer MCR301) with a parallel plate (PP12) having a diameter of 12 mm under the conditions of 120°C, an angular frequency of 0.1 rad / sec, and a strain of 0.1%.

[0021] The screen printing ink composition according to the present invention preferably contains a rubber component in an amount of 15.0 to 60.0 mass %, more preferably 20.0 to 50.0 mass %, and even more preferably 28.0 to 40.0 mass %.

[0022] When the screen printing ink composition according to the present invention contains a plasticizer in the rubber-forming components, the screen printing ink composition according to the present invention preferably contains 1.0 to 20.0 mass %, more preferably 3.0 to 18.0 mass %, and even more preferably 5.0 to 15.0 mass % of the plasticizer.

[0023] Furthermore, the screen printing ink composition according to the present invention preferably contains 15.0 to 80.0 mass %, more preferably 30.0 to 80.0 mass %, even more preferably 35.0 to 65.0 mass %, and even more preferably 40.0 to 60.0 mass %, of the (a) rubber-forming component.

[0024] In the screen printing ink composition according to the present invention, the (b) crosslinking agent is not particularly limited as long as it is capable of crosslinking the rubber component in the (a) rubber-forming component, and may be appropriately selected from known crosslinking agents. A thermal crosslinking agent is preferable.

[0025] In the screen printing ink composition according to the present invention, specific examples of the crosslinking agent (b) include one or more types selected from the group consisting of sulfur, organic peroxides, quinoid compounds, phenolic resins, amines, metal oxides, and polyol compounds.

[0026] The screen printing ink composition according to the present invention preferably contains 1.5 to 15.0 mass %, more preferably 2.0 to 10.0 mass %, and even more preferably 3.0 to 8.0 mass %, of the (b) crosslinking agent.

[0027] When the screen printing ink composition according to the present invention contains the crosslinking agent (b) within the above range, the rubber component in the rubber-forming component (a) can be crosslinked suitably.

[0028] The screen printing ink composition according to the present invention contains (c) a main solvent that dissolves the rubber-forming component.

[0029] In the screen printing ink composition according to the present invention, the main solvent for dissolving the rubber-forming component (c) is not particularly limited as long as it is capable of dissolving the rubber-forming component (c). For example, when the rubber component is ethylene-propylene-diene rubber (EPDM), the main solvent can be one or more selected from aromatic hydrocarbons such as toluene, benzene, mesitylene, and xylene, and aliphatic hydrocarbons such as hexane, heptane, octane, nonane, decane, undecane, and dodecane.

[0030] In this application, "dissolving the rubber-forming component" means that a 1 mm thick sheet of the rubber-forming component is cut into a 5 mm x 5 mm square, the resulting cut pieces are added to a main solvent in a weight ratio of 1:9, stirred with a stirrer for 12 hours, and then allowed to stand for a further 12 hours, after which no residual material is found when visually observed.

[0031] In the screen printing ink composition according to the present invention, the (d) poor solvent which is soluble in the main solvent but insoluble in the rubber-forming component can be appropriately selected depending on the type of the (a) rubber-forming component. For example, when the rubber component is ethylene-propylene-diene rubber (EPDM), one or more solvents selected from ester-based solvents such as diethylene glycol monoethyl ether acetate and butyl lactate, ether-based solvents, and the like can be used.

[0032] In the present application, "dissolves in the main solvent" means that when the main solvent and the poor solvent are mixed in a volume ratio of 1:1 in a glass container and allowed to stand for 12 hours, no emulsification or separation occurs when observed with the naked eye.

[0033] In addition, in the present application, "not dissolving in the rubber-forming component" means that when a rubber-forming component containing 10 to 50 mass % of a colored filler such as carbon black and a poor solvent are charged in a weight ratio of 1:9, stirred with a stirrer for 12 hours, and then allowed to stand for a further 12 hours, the rubber-forming component (colored by the filler) is not dispersed as determined by visual observation.

[0034] The screen printing ink composition according to the present invention contains (d) a poor solvent in addition to (c) a main solvent, thereby improving the cohesiveness of the rubber-forming components in the ink composition, reducing the adhesion of the ink composition to the screen stencil, and improving its extrudability, thereby making it possible to effectively suppress the occurrence of printing sagging.

[0035] In the screen printing ink composition according to the present invention, the boiling points of (c) the main solvent and (d) the poor solvent are not particularly limited as long as they have little effect on continuous printability due to drying during screen printing and are not difficult to dry. The boiling points are preferably 170 to 220°C, more preferably 185 to 220°C, and even more preferably 200 to 220°C.

[0036] In the screen printing ink composition according to the present invention, the content ratio of (c) the main solvent that dissolves the rubber-forming component to (d) the poor solvent that dissolves in the main solvent but insoluble in the rubber-forming component, expressed by mass ratio of (c) the main solvent that dissolves the rubber-forming component:(d) the poor solvent that dissolves in the main solvent but insoluble in the rubber-forming component, is preferably 80:20 to 97:3, more preferably 80:20 to 96:4, and even more preferably 85:15 to 95:5.

[0037] In the screen printing ink composition according to the present invention, the content ratio of (c) the main solvent that dissolves the rubber-forming component and (d) the poor solvent that dissolves in the main solvent but not in the rubber-forming component is within the above range, thereby improving the cohesiveness of the rubber-forming component in the ink composition, reducing the adhesion of the ink composition to the screen stencil and improving its extrudability, thereby effectively suppressing the occurrence of printing sagging.

[0038] The screen printing ink composition according to the present invention may contain, in addition to (a) a rubber-forming component, (b) a crosslinking agent, (c) a main solvent that dissolves the rubber-forming component, and (d) a poor solvent that dissolves in the main solvent but not in the rubber-forming component, one or more agents selected from the group consisting of a filler, a plasticizer, a dispersant, a crosslinking aid, an antifoaming agent, a foaming agent, and the like.

[0039] The screen printing ink composition according to the present invention preferably contains the main solvent (c) and the poor solvent (d) in a total amount of 15.0 to 70.0 mass %, preferably 20.0 to 70.0 mass %, more preferably 35.0 to 65.0 mass %, and even more preferably 40.0 to 60.0 mass %.

[0040] The screen printing ink composition according to the present invention has a viscosity (0.1 / s) measured with an E-type viscometer at a temperature of 25°C of 300 to 50,000 Pa·s, preferably 300 to 10,000 Pa·s, more preferably 400 to 1,000 Pa·s, and even more preferably 450 to 900 Pa·s.

[0041] When the screen printing ink composition according to the present invention has a viscosity (0.1 / s) measured using an E-type viscometer at a temperature of 25°C within the above range, the occurrence of printing sagging can be more effectively suppressed even in the case of forming a thick printed matter.

[0042] In this application, the viscosity (0.1 / s) obtained by an E-type viscometer at a temperature of 25°C means the viscosity measured using an E-type viscometer (Anton Paar rheometer MCR301) at a temperature of 25°C and a shear rate of 0.1 / s.

[0043] The screen printing ink composition according to the present invention has a viscosity (10 / s) measured at 25° C. using an E-type viscometer of 50 to 1500 Pa·s, preferably 100 to 800 Pa·s, and more preferably 100 to 500 Pa·s.

[0044] When the viscosity (10 / s) of the screen printing ink composition according to the present invention, measured using an E-type viscometer at a temperature of 25° C., falls within the above range, screen printing can be performed while ensuring favorable printability.

[0045] The screen printing ink composition according to the present invention preferably has a loss tangent (0.1 rad / s) measured at 25° C. using an E-type viscometer of 10.0 to 20.0, more preferably 10.0 to 17.0, and even more preferably 10.0 to 13.0.

[0046] In the screen printing ink composition according to the present invention, the loss tangent (0.1 rad / s) measured at 25°C using an E-type viscometer falls within the above range, so that the adhesion of the ink composition to the screen stencil is reduced and the extrusion properties are improved, thereby making it possible to effectively suppress the occurrence of printing sagging.

[0047] In the screen printing ink composition according to the present invention, the loss tangent (0.1 rad / s) measured with an E-type viscometer at a temperature of 25° C. can be easily controlled by adjusting the types and blending ratios of (c) the main solvent and (d) the poor solvent relative to (a) the rubber-forming component and (b) the crosslinking agent.

[0048] In the present application, the loss tangent (0.1 rad / s) obtained with an E-type viscometer at a temperature of 25°C means a value obtained by stirring the screen printing ink composition for 12 hours or more, visually confirming that there are no undispersed matters or undissolved residues, and then vacuum degassing the composition to remove internal air bubbles, and then measuring the value using an E-type viscometer (rheometer MCR301 manufactured by Anton Paar) using parallel plates (PP25) with a diameter of 25 mm, under the following conditions: sample thickness 1 mm, 25°C, angular frequency 0.1 radians / second, and strain 0.1%.

[0049] The method for preparing the screen printing ink composition according to the present invention is not particularly limited. The screen printing ink composition according to the present invention can be prepared, for example, by taking desired amounts of each of (a) the rubber-forming component, (b) the crosslinking agent, and, if necessary, other components, and kneading them using a known kneading machine such as an Intermix, kneader, or Banbury mixer, or a known kneading device such as an open roll, adding to the kneaded mixture obtained (c) a main solvent that dissolves the rubber-forming component, and (d) a poor solvent that dissolves in the main solvent but is insoluble in the rubber-forming component, and further stirring the mixture using a known stirrer.

[0050] The method of screen printing using the screen printing ink composition according to the present invention is as described in detail below in the description of the method of producing a printed matter according to the present invention.

[0051] The screen printing ink composition according to the present invention can be suitably used when printing thick objects by screen printing. The screen printing ink composition according to the present invention can be suitably used, for example, when forming a gasket by screen printing, and can be more suitably used when forming a gasket for a fuel cell by screen printing.

[0052] According to the present invention, it is possible to provide an ink composition for screen printing which is unlikely to cause printing defects or surface roughness in printed matter even when a thick printed matter is formed.

[0053] Next, a method for producing a printed matter according to the present invention will be described. The method for producing a printed matter according to the present invention is characterized in that the screen printing ink composition according to the present invention is screen-printed, and then a curing treatment is performed to form a printed matter.

[0054] The details of the screen printing ink composition according to the present invention, which is used in the method for producing a printed matter according to the present invention, are as described above.

[0055] The method for producing a printed matter according to the present invention can be carried out, for example, by the following steps (1) to (3). (1) As shown in the schematic cross-sectional view of Figure 1, a screen plate S having a mask M with a predetermined pattern of openings O for applying paste corresponding to the planar shape of the print to be obtained is placed on the underside of a screen S1 made of stainless steel mesh or the like, and a substrate B is positioned and abutted against the underside of the screen plate S. (2) The paste 1 (screen printing ink composition according to the present invention) supplied to the top of the screen plate S is pushed out into the paste application opening O of the mask M by the movement of the squeegee R and adhered to the surface of the substrate B. The substrate B is then separated from the screen plate S, and a paste application layer P is formed on the surface of the substrate B in a predetermined printing pattern, as shown in the schematic cross-sectional view corresponding to Figure 2. (3) The coating layer P is cured by heat or the like to form a desired printed matter on the substrate 1.

[0056] The thickness of the printed matter can be easily controlled by adjusting the thickness of the screen plate. The thickness of the printed matter obtained by the production method according to the present invention is preferably 90 μm or more, more preferably 100 μm or more, even more preferably 100 to 150 μm, and even more preferably 100 to 120 μm.

[0057] In the present application, the thickness of a printed matter refers to the maximum value when a cross section of the printed matter is cut out and measured at eight points using a microscope. In the method for producing a printed matter according to the present invention, the screen printing ink composition according to the present invention is used, so that even if the thickness of the resulting printed matter is thick, it is possible to easily form a printed matter while suppressing the occurrence of printing defects such as printing sagging and surface roughness.

[0058] In the method for producing a printed matter according to the present invention, an example of the printed matter obtained is a gasket, and an example of the gasket is a gasket for a fuel cell.

[0059] When the printed matter obtained by the manufacturing method according to the present invention is a gasket for a fuel cell, the substrate on which the printed matter is formed can be a separator constituting a fuel cell, or the like. When the substrate is a separator, an integrated product of the separator and the gasket can be easily formed.

[0060] According to the present invention, a method for producing a printed matter can be provided that can easily form a printed matter while suppressing the occurrence of printing defects such as print sagging and surface roughness, even if the resulting printed matter is thick.

[0061] The present invention will now be described in more detail with reference to examples, but these are merely illustrative and do not limit the present invention.

[0062] Example 1 As shown in Table 1, (a) 31.3 parts by weight of ethylene propylene diene rubber 1 (EPDM1) as a rubber-forming component, (b) 3.1 parts by weight of a crosslinking agent, and 12.5 parts by weight of carbon black were kneaded with an open roll to prepare a kneaded mixture, and (c) 47.7 parts by weight of dodecane as a main solvent and (d) 5.3 parts by weight of diethylene glycol monoethyl ether acetate (EDGAC) as a poor solvent were further added to the kneaded mixture and stirred with a stirrer to prepare a screen printing ink composition. The polymer viscosity (0.1 rad / s) of the rubber-forming component was 237000 Pa·s. The resulting screen printing ink composition had a loss tangent (0.1 rad / s) of 10.6 at 25°C using an E-type viscometer, a viscosity (0.1 / s) of 886 Pa s at 25°C using an E-type viscometer, and a viscosity (10 / s) of 584 Pa s at 25°C using an E-type viscometer.

[0063] Using the obtained screen printing ink composition, screen printing was performed under the following conditions in the same manner as in Example 1 to obtain a gasket with a thickness of 102 μm, and the adhesion rate to the screen plate and the number of surface roughness spots on the obtained print were measured. The results are shown in Table 1.

[0064] (Screen printing method) The ink composition for screen printing was applied onto a screen (165 mesh / inch) and filled into the openings of the screen with a scraper, and then the ink composition filled into the openings was transferred to a substrate with a squeegee. The transferred ink composition was dried at 120°C for 30 minutes in a hot air oven, and then heated at 200°C for 30 minutes to crosslink and harden, thereby obtaining the desired gasket.

[0065] (Adhesion rate to screen) Using a microscope, any four points on the printing portion of the screen used in the above screen printing were observed at a magnification of 30 times, and the degree of adhesion to the screen at each observed point was calculated according to the following formula. Degree of adhesion to the screen plate = (number of screen apertures to which the ink composition is attached / total number of screen apertures excluding the apertures around the observation area) x 100 Then, the arithmetic mean value of the above adhesion degree was calculated as the adhesion ratio of the ink composition to the screen stencil, and the adhesion inhibition ability of the ink composition to the screen stencil was evaluated according to the following criteria. 〇: The adhesion rate to the screen is 0% to 30%. ×: The adhesion rate to the screen is more than 30% and is 100% or less. The results are shown in Table 1.

[0066] (Number of rough surfaces) Using a microscope, any location on the gasket surface obtained by the above screen printing was observed at 5x magnification, and the number of surface roughness at the observed location was calculated as (number of surface roughness such as screen marks / total observed area) x 100. The results are shown in Table 1.

[0067] Example 2 As shown in Table 1, (a) 28.5 parts by weight of ethylene propylene diene rubber 1 (EPDM1) and 9.1 parts by weight of plasticizer 1 as rubber-forming components, (b) 2.8 parts by weight of crosslinking agent, and 11.4 parts by weight of carbon black were kneaded using an open roll to prepare a kneaded mixture, and (c) 43.4 parts by weight of dodecane as the main solvent and (d) 4.8 parts by weight of diethylene glycol monoethyl ether acetate (EDGAC) as the poor solvent were further added to the kneaded mixture and stirred with a stirrer to prepare a screen printing ink composition. The polymer viscosity (0.1 rad / s) of the rubber-forming component was 35,300 Pa·s. The resulting screen printing ink composition had a loss tangent (0.1 rad / s) of 16.5, a viscosity (0.1 / s) of 541 Pa s, and a viscosity (10 / s) of 328 Pa s, all measured using an E-type viscometer at 25°C.

[0068] Using the obtained screen printing ink composition, screen printing was performed in the same manner as in Example 1 to obtain a gasket with a thickness of 124 μm, and the adhesion rate to the screen stencil and the number of surface roughness spots in the obtained print were measured in the same manner as in Example 1. The results are shown in Table 1.

[0069] Comparative Example 1 As shown in Table 1, (a) 31.3 parts by weight of ethylene propylene diene rubber 1 (EPDM1) as a rubber-forming component, (b) 3.1 parts by weight of a crosslinking agent, and 12.5 parts by weight of carbon black were kneaded with an open roll to prepare a kneaded mixture, and (c) 53.0 parts by weight of dodecane as a main solvent was further added to the kneaded mixture and stirred with a stirrer to prepare a screen printing ink composition. The polymer viscosity (0.1 rad / s) of the rubber-forming component was 237000 Pa·s. The resulting screen printing ink composition had a loss tangent (0.1 rad / s) of 22.0 as measured by an E-type viscometer at 25°C, a viscosity (0.1 / s) of 596 Pa s as measured by an E-type viscometer at 25°C, and a viscosity (10 / s) of 375 Pa s as measured by an E-type viscometer at 25°C.

[0070] Using the obtained screen printing ink composition, screen printing was performed to obtain a gasket with a thickness of 106 μm in the same manner as in Example 1, and the adhesion rate to the screen stencil and the number of surface roughness spots in the obtained print were measured in the same manner as in Example 1. The results are shown in Table 1.

[0071] Example 3 As shown in Table 1, (a) 35.9 parts by weight of ethylene propylene diene rubber 2 (EPDM2) as a rubber-forming component, (b) 3.6 parts by weight of a crosslinking agent, and 14.4 parts by weight of carbon black were kneaded with an open roll to prepare a kneaded mixture, and (c) 41.5 parts by weight of dodecane as a main solvent and (d) 4.6 parts by weight of diethylene glycol monoethyl ether acetate (EDGAC) as a poor solvent were further added to the kneaded mixture and stirred with a stirrer to prepare a screen printing ink composition. The polymer viscosity (0.1 rad / s) of the rubber-forming component was 11,900 Pa·s. The resulting screen printing ink composition had a loss tangent (0.1 rad / s) of 19.0 as measured by an E-type viscometer at 25°C, a viscosity (0.1 / s) of 804 Pa s as measured by an E-type viscometer at 25°C, and a viscosity (10 / s) of 532 Pa s as measured by an E-type viscometer at 25°C.

[0072] Using the obtained screen printing ink composition, screen printing was performed to obtain a gasket with a thickness of 117 μm in the same manner as in Example 1, and the adhesion rate to the screen stencil and the number of surface roughness spots in the obtained print were measured in the same manner as in Example 1. The results are shown in Table 1.

[0073] Comparative Example 2 As shown in Table 1, (a) 23.8 parts by weight of ethylene propylene diene rubber 3 (EPDM3) as a rubber-forming component, (b) 2.4 parts by weight of a crosslinking agent, and 9.5 parts by weight of carbon black were kneaded with an open roll to prepare a kneaded mixture, and (c) 64.3 parts by weight of dodecane as the main solvent was further added to the kneaded mixture and stirred with a stirrer to prepare a screen printing ink composition. The polymer viscosity (0.1 rad / s) of the rubber-forming component was 300,000 Pa·s. The resulting screen printing ink composition had a loss tangent (0.1 rad / s) of 25.0, a viscosity (0.1 / s) of 572 Pa s, and a viscosity (10 / s) of 349 Pa s, all measured using an E-type viscometer at 25°C.

[0074] Using the obtained screen printing ink composition, screen printing was performed to obtain a gasket with a thickness of 65 μm in the same manner as in Example 1, and the adhesion rate to the screen stencil and the number of surface roughness spots in the obtained print were measured in the same manner as in Example 1. The results are shown in Table 1.

[0075] Example 4 As shown in Table 1, (a) 31.3 parts by weight of ethylene propylene diene rubber 2 (EPDM2) as a rubber-forming component, (b) 3.1 parts by weight of a crosslinking agent, and 12.5 parts by weight of carbon black were kneaded with an open roll to prepare a kneaded mixture, and (c) 45.1 parts by weight of dodecane as a main solvent and (d) 8.0 parts by weight of butyl lactate as a poor solvent were further added to the kneaded mixture and stirred with a stirrer to prepare an ink composition for screen printing. The polymer viscosity (0.1 rad / s) of the rubber-forming component was 237000 Pa·s. The resulting screen printing ink composition had a loss tangent (0.1 rad / s) of 10.7 at 25°C using an E-type viscometer, a viscosity (0.1 / s) of 850 Pa s at 25°C using an E-type viscometer, and a viscosity (10 / s) of 438 Pa s at 25°C using an E-type viscometer.

[0076] Using the obtained screen printing ink composition, screen printing was performed to obtain a gasket with a thickness of 91 μm in the same manner as in Example 1, and the adhesion rate to the screen stencil and the number of surface roughness spots in the obtained print were measured in the same manner as in Example 1. The results are shown in Table 1.

[0077] Example 5 As shown in Table 1, (a) 28.0 parts by weight of ethylene propylene diene rubber 1 (EPDM1) as a rubber-forming component, (b) 2.8 parts by weight of a crosslinking agent, and 11.2 parts by weight of carbon black were kneaded with an open roll to prepare a kneaded mixture, and (c) 52.2 parts by weight of dodecane as a main solvent and (d) 5.8 parts by weight of diethylene glycol monoethyl ether acetate (EDGAC) as a poor solvent were further added to the kneaded mixture and stirred with a stirrer to prepare a screen printing ink composition. The polymer viscosity (0.1 rad / s) of the rubber-forming component was 237000 Pa·s. The resulting screen printing ink composition had a loss tangent (0.1 rad / s) of 17.0 at 25°C using an E-type viscometer, a viscosity (0.1 / s) of 310 Pa s at 25°C using an E-type viscometer, and a viscosity (10 / s) of 210 Pa s at 25°C using an E-type viscometer.

[0078] Using the obtained screen printing ink composition, screen printing was performed to obtain a gasket with a thickness of 102 μm in the same manner as in Example 1, and the adhesion rate to the screen stencil and the number of surface roughness spots in the obtained print were measured in the same manner as in Example 1. The results are shown in Table 1.

[0079] Comparative Example 3 As shown in Table 1, (a) 28.0 parts by weight of ethylene propylene diene rubber 1 (EPDM1) as a rubber-forming component, (b) 2.8 parts by weight of a crosslinking agent, and 11.2 parts by weight of carbon black were kneaded with an open roll to prepare a kneaded mixture, and (c) 58.0 parts by weight of dodecane as a main solvent was further added to the kneaded mixture and stirred with a stirrer to prepare a screen printing ink composition. The polymer viscosity (0.1 rad / s) of the rubber-forming component was 237000 Pa·s. The resulting screen printing ink composition had a loss tangent (0.1 rad / s) of 47.1, a viscosity (0.1 / s) of 154 Pa s, and a viscosity (10 / s) of 127 Pa s, all measured using an E-type viscometer at 25°C.

[0080] Using the obtained screen printing ink composition, screen printing was performed to obtain a gasket with a thickness of 81 μm in the same manner as in Example 1, and the adhesion rate to the screen stencil and the number of surface roughness spots in the obtained print were measured in the same manner as in Example 1. The results are shown in Table 1.

[0081] Comparative Example 4 As shown in Table 1, (a) 31.4 parts by weight of ethylene propylene diene rubber 1 (EPDM1) as a rubber-forming component, (b) 3.1 parts by weight of a crosslinking agent, and 12.5 parts by weight of carbon black were kneaded with an open roll to prepare a kneaded mixture, and (c) 53.0 parts by weight of decane as the main solvent was further added to the obtained kneaded mixture and stirred with a stirrer to prepare a screen printing ink composition. The polymer viscosity (0.1 rad / s) of the rubber-forming component was 237000 Pa·s. The resulting screen printing ink composition had a loss tangent (0.1 rad / s) of 17.2, a viscosity (0.1 / s) of 269 Pa s, and a viscosity (10 / s) of 201 Pa s, all measured using an E-type viscometer at 25°C.

[0082] Using the obtained screen printing ink composition, screen printing was performed to obtain a gasket with a thickness of 119 μm in the same manner as in Example 1, and the adhesion rate to the screen stencil and the number of surface roughness spots in the obtained print were measured in the same manner as in Example 1. The results are shown in Table 1.

[0083] Example 6 As shown in Table 1, (a) 28.5 parts by weight of ethylene propylene diene rubber 1 (EPDM1) and 9.1 parts by weight of plasticizer 2 as rubber-forming components, (b) 2.8 parts by weight of crosslinking agent, and 11.4 parts by weight of carbon black were kneaded with an open roll to prepare a kneaded mixture, and (c) 43.4 parts by weight of dodecane as the main solvent and (d) 4.8 parts by weight of diethylene glycol monoethyl ether acetate (EDGAC) as the poor solvent were further added to the obtained kneaded mixture and stirred with a stirrer to prepare a screen printing ink composition. The polymer viscosity (0.1 rad / s) of the rubber-forming component was 31,300 Pa·s. The resulting screen printing ink composition had a loss tangent (0.1 rad / s) of 19.9, a viscosity (0.1 / s) of 439 Pa s, and a viscosity (10 / s) of 287 Pa s, all measured using an E-type viscometer at 25°C.

[0084] Using the obtained screen printing ink composition, screen printing was performed to obtain a gasket with a thickness of 91 μm in the same manner as in Example 1, and the adhesion rate to the screen stencil and the number of surface roughness spots in the obtained print were measured in the same manner as in Example 1. The results are shown in Table 1.

[0085] [Table 1]

[0086] As shown in Table 1, the screen printing ink compositions obtained in Examples 1 to 6 contain (a) a rubber-forming component and (b) a crosslinking agent, and have a viscosity (0.1 / s) of 300 to 50,000 Pa·s as measured by an E-type viscometer at a temperature of 25°C and a viscosity (10 / s) of 50 to 1,500 Pa·s as measured by an E-type viscometer at a temperature of 25°C. In addition, the screen printing ink compositions contain, as the solvents constituting the ink compositions, (c) a main solvent that dissolves the rubber-forming component, and (d) a poor solvent that dissolves in the main solvent but not in the rubber-forming component. This controls the loss tangent (0.1 rad / s) as measured by an E-type viscometer to 10.0 to 20.0, thereby effectively improving the cohesiveness of the rubber-forming component in the ink composition, and suppresses the amount of adhesion of the ink composition during screen printing, thereby improving its extrusion property. Furthermore, as shown in Table 1, the screen printing ink compositions obtained in Examples 1 to 3 contain the above-mentioned (c) main solvent and (d) poor solvent as the solvents constituting the screen printing ink composition, and as a result, the above-mentioned (d) poor solvent volatilizes during the drying treatment after screen printing or during the heat curing treatment of the (b) crosslinking agent, thereby reducing the viscosity of the extrudate when it is dried compared to immediately after extrusion through the screen stencil, thereby easily improving the leveling property (surface smoothness) and reducing the number of surface roughness.

[0087] In contrast, as shown in Table 1, the comparative screen printing ink compositions obtained in Comparative Examples 1 to 4 do not contain (c) a main solvent that dissolves the rubber-forming components, nor (d) a poor solvent that dissolves in the main solvent but not in the rubber-forming components, and therefore the amount of ink composition adhered during screen printing is high. In addition, the leveling property (surface smoothness) of the extruded product cannot be improved after extrusion through the screen stencil, and the number of surface roughness particles is high. [Industrial Applicability]

[0088] Effects of the Invention According to the present invention, it is possible to provide an ink composition for screen printing that is unlikely to cause printing defects or surface roughness in printed matter even when a thick printed matter is formed, and a method for producing a printed matter using the ink composition for screen printing. [Explanation of symbols]

[0089] 1 Paste M Mask S-screen version S1 Screen O opening B Substrate R Squeegee P Paste coating layer

Claims

1. (a) ethylene propylene diene rubber; (b) a crosslinking agent; and (c) a main solvent for dissolving the ethylene propylene diene rubber; (d) a poor solvent that dissolves in the main solvent but does not dissolve in the ethylene propylene diene rubber; Including, A viscosity (0.1 / s) measured using an E-type viscometer at a temperature of 25°C is 300 to 50,000 Pa·s, A viscosity (10 / s) measured using an E-type viscometer at a temperature of 25°C is 50 to 1500 Pa·s, The loss tangent (0.1 rad / s) measured with an E-type viscometer at a temperature of 25°C is 10.0 to 20.

0.

1. An ink composition for screen printing comprising:

2. A method for producing a printed matter, comprising screen printing the ink composition for screen printing according to claim 1 and then curing the same to form a printed matter.

3. The method for producing a printed article according to claim 2, wherein the printed article is a gasket.

Citation Information

Patent Citations

  • Carving gravure ink and preparation method and safety product thereof

    CN104231733A

  • Fluororubber-based screen coating fluid

    JP1996100147A

  • Cylinder head gasket

    JP1997296865A

  • Gasket material and its production

    JP2000345139A

  • Gasket, and gasket material

    JP2003278917A